Methane-induced explosions in vented enclosures. (July 2017) - Sezer, Hayri; Kronz, Francis; Akkerman, V'yacheslav; Rangwala, Ali S.
Abstract: Explosions in enclosures leading to devastating accidents occur in various industrial, commercial, and residential occupancies. To relieve the effect of such explosions, vents of various sizes and geometry are designed. In this study, a computational model for gas explosions venting, developed and validated on hydrogen explosion by Ugarte et al. [ Process Safety and Environmental Protection, 99, (2016) 167–174] is extended to vented explosion scenarios for methane. The model is based on a time-dependent set of ordinary differential equations whose solution allows prediction of temperature, pressure and vented mass transients resulting from the explosion of methane-air in vented enclosures. The model is compared to the experiments available in the literature and NFPA 68 standards at different vent areas and equivalent ratios. The influence of gas equivalence ratio and vent size on the rate of pressure rise is analyzed. A framework for the gas explosion vent design using the fundamental laminar burning velocity of a gas-air mixture is also discussed. Highlights: Only time-dependent set of ordinary differential equations in explosion venting analyzer. EVA predicts the temperature, pressure and vented mass transients. EVA software predicts the over pressure transients with accuracy similar to CFD models. NFPA 68 predicts overpressure an order of magnitude higher than that of experiments and EVA predictions.